IMPROVING MOOSE POPULATION ESTIMATES IN RUSSIA: ACCOUNTING FOR DISTANCE BETWEEN RESIDENTIAL AREAS AND TRACK SIGHTINGS - Glushkov, Vladimir M. (Lakehead University, 2013)
Moose (Alces alces) population density in the Kirov region of Russia is often overestimated when using the relationship between the distance between a residential area and the initial sighting of moose tracks. This paper presents a modified approach to provide better estimates when using this techinique. Statistically valid density estimation techniques, standardization of estimation points and routes, landscape characteristics, and time have been addressed in the new approach. Moose density is estimated once annually based on the distance to the first track, and annual surveys should maintain a like protocol. This improved method will provide more accurate population density estimates critical to prevent regional overharvest of moose.